COVID-19 as a catalyst to inspire learning and create fresh, meaningful interpersonal interactions : a case study of positive psychology in higher education - Hall, Deborah A; Tetisya Ragunathan; Wong, Leonard Wui-Loong; Low, Jasmine; Choong, Sulynn (Penerbit Universiti Kebangsaan Malaysia, 2021)
Increasingly, school curricula are embedding the principles of positive psychology to enhance wellbeing. To our knowledge, very few universities have taken this step. Since 2018, Heriot-Watt University Malaysia has offered a distinctive programme to develop students’ personal wellbeing and resilience together with academic performance and personal effectiveness. This programme includes four workshops focused on identifying purpose and fostering social responsibility. To overcome the COVID-19 restrictions on teaching, these workshops were redesigned for small-group web-based coaching. This study tests two propositions: i) the workshops achieved wider unintended benefits to students’ sense of belonging, and ii) the concept of belonging derived from research in secondary schools is meaningful in a university setting. Primary data was gathered using semi-structured interviews (n=8). Interview transcripts were analysed using a deductive approach informed by a validated construct of school belonging comprising ten factors. Results showed how the workshops cultivated belonging, especially through teacher support and students’ personal characteristics, consistent with previous school-based research. Regarding their contributions to belonging, the pandemic situation seemed to heighten the importance of peer support and downplay the importance of extracurricular activities. Despite obvious challenges, COVID-19 has been a catalyst to inspire learning and create fresh, meaningful interpersonal interactions in higher education.